Pest Management in Universiti Tun Hussein Onn Malaysia Natural History Repository - Arney Sapaat; Maryati Mohamed; Mohd. Noh Dalimin (Journal of Tropical Biodiversity and Biotechnology, 2018)
Under the Malaysian Universities Act 1971, Higher Learning Institutions are encouraged to set up museums that could support teaching and learning at the institution. With that provision, the Universiti Tun Hussein Onn Malaysia (UTHM) Natural History Repository was formed in 2014, to support the newly developed BSc Program called Biodiversity and Conservation. Under the Faculty of Applied Science and Technology, Centre of Research - Sustainable Uses of Natural Resources (CoR-SUNR), develops and organizes the repository. Currently the repository is sited at a shoplot building in Parit Raja Campus that had been modified as part of campus expansion plan. The process of converting this shoplot building into functional gallery/storage space introduced a new challenge in pest management. The goals were to ensure whatever pests already present are eradicated, determine ways to seal out future pests, stabilize the condition to decrease pest infestation, and establish a monitoring program. Baseline pest data were collected via trapping throughout the repository spaces before, during, and after retrofit construction. Data from trapping were used to assess pest problems, and actions to eliminate these pests were initiated. A year-long survey of pests was performed after staff and collections occupied the building. The results showed variation in pest diversity and populations.  Having succeeded in controlling insects pest problems at UTHM Natural History Repository would lead to better teaching/learning experience for graduates as well as promoting public awareness and education especially among young public on biodiversity.Under the Malaysian Universities Act 1971, Higher Learning Institutions are encouraged to set up museums that could support teaching and learning at the institution. With that provision, the Universiti Tun Hussein Onn Malaysia (UTHM) Natural History Repository was formed in 2014, to support the newly developed BSc Program called Biodiversity and Conservation. Under the Faculty of Applied Science and Technology, Centre of Research - Sustainable Uses of Natural Resources (CoR-SUNR), develops and organizes the repository. Currently the repository is sited at a shoplot building in Parit Raja Campus that had been modified as part of campus expansion plan. The process of converting this shoplot building into functional gallery/storage space introduced a new challenge in pest management. The goals were to ensure whatever pests already present are eradicated, determine ways to seal out future pests, stabilize the condition to decrease pest infestation, and establish a monitoring program. Baseline pest data were collected via trapping throughout the repository spaces before, during, and after retrofit construction. Data from trapping were used to assess pest problems, and actions to eliminate these pests were initiated. A year-long survey of pests was performed after staff and collections occupied the building. The results showed variation in pest diversity and populations.  Having succeeded in controlling insects pest problems at UTHM Natural History Repository would lead to better teaching/learning experience for graduates as well as promoting public awareness and education especially among young public on biodiversity.